Археологічні дослідження Скалатського замку у 2008 році - Строцень, Л.Д. (Археологія і давня історія України, 2010)
Стаття знайомить з результатами розкопок
Скалатського замку, які проводились ДП ОАСУ «Подільська археологія» у 2008 році. Під час досліджень виявлено залишки господарських приміщень, житлової будівлі, палацу XVII —XVIII ст. The article acquaint us with results of the archaeological
in Scalat’s Castle. This excavation have been
made by organization «Podilska archaeology» in 2008
year. While excavation have found remains of economical
building (XVII—XVIII ct.) and house building
XVII c. On the base of this building have built the palace in XVII c.